Cutaneous Vasculitis in a Patient with Crohn's Disease Treated with Adalimumab. Issue 1 (28th November 2016) - Cury, Didia B.; de Souza, Alexandre W. S.; Vianna, Giovanni A.; Odashiro, Danilo; Farias, Alex; Moss, Alan C.
Abstract : Article first published online 28 November 2016.